Plants used for Treatment of Bone Fractures and Bone Related Diseases in Garhwal Region of Uttarakhand State in India - Kala, Chandra Prakash (Indian Forester, 2020)
The present study aims to document and analyze the traditional knowledge, as practiced by the local herbal healers, on the use ofplants for treatment of bone fractures and related disorders in Garhwal region of Uttarakhand Himalaya that endows rich bio-cultural diversity and ethnobotanical practices. This may help to safeguard the fading wealth of ethnobotanical practices and knowledge. Field surveys were undertaken forgathering information on availability and uses ofplants for treatment of bone related disorders. A total 45 plant species belonging to 33 families were documented, which were used to treat bone fractures, sciatica, arthritis, rickets,joint pain andjoint dislocation. Among all plant form trees were used in highest number, followed by herbs and shrubs. The highest number of species was discovered for the treatment ofbone fractures, followed by sciatica and dislocatedjoints. The traditional practices, as adopted by herbal healers for treatment of bone related disorders, comprise ofbone setting, application ofherbalmedicine, traditional splinting and massage.